‘IN PLACE’: Making the British Library’s Collections ‘Local’ as well as ‘National’ - Shaw, Graham (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
‚In Place’ is the name of a government-funded digitisation project currently underway at the British Library which when completed in 2004 will be the premier web-showcase for the Library’s collections. It focuses particularly on the Library’s holdings relating to the United Kingdom itself, and is targeted specifically at ‚lifelong learners’, although many of the items being digitised for the first time will equally be of interest to the Library’s core academic clientele.